Every Farmer Should Be Awakened. Liberty hyde bailey's vision of agricultural extension work. - Peters, Scott J. (Berkeley, California US: The Agricultural History Society by The University of California Press)
ESTADOS UNIDOS
Keywords: ESTADOS UNIDOS DE AMÉRICA; HISTORIA AGRARIA; AGRICULTURA